Peripheral Blood Smear Eosinophil Differential Count Comparison in Patients with Skabies and After One Week Recovered from Scabies - Patriyuni, Tri; Nasution, Sri Wahyuni; Chiuman, Linda (Fakultas Kedokteran Universitas Malikussaleh, 2023)
Scabies is a skin infection disease caused by infestation and sensitization of the mite Sarcoptes scabiei, easily transmitted from person to person. Immune response has a crucial role in secondary complications and morbidity of individuals with scabies. Eosinophil is essential in defense against parasites but also contribute to tissue dysfunction and damage in allergic diseases. The purpose of this study was to compare the peripheral blood eosinophils differential count of patients while suffering from scabies and one week after recovered from scabies. This is an analytic comparative study with a cohort design. Sample size of 30 subjects calculated with sample size formula for paired categorical-numeric analytic research. Wilcoxon test was performed for data analysis due to the data not normally distributed. The result of this study showed the mean peripheral blood differential eosinophil count of patients while suffering from scabies was 3,6% (3% - 5%) whereas one week after recovered from scabies was 2,37% (2% - 3%). There was signicant difference in the peripheral blood differential eosinophils count between patients while suffering from scabies and one week after recovered from scabies with a p value <0.05.